2017
DOI: 10.1093/humrep/dew343
|View full text |Cite
|
Sign up to set email alerts
|

Human foetal ovary shares meiotic preventing factors with the developing testis

Abstract: This research was supported by the Université Paris Diderot-Paris 7 and Université Paris-Sud, CEA, INSERM, and Agence de la Biomédecine. The authors declare no conflict of interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 46 publications
1
27
0
Order By: Relevance
“…However, in other organisms, including humans, Cyp26b1 expression is not downregulated during meiosis (Frydman et al, 2017). Cyp26b1 has a central role in suppressing meiosis in embryonic testes in mice, and is not expressed in developing ovaries during meiotic initiation.…”
Section: Future Directionsmentioning
confidence: 97%
See 1 more Smart Citation
“…However, in other organisms, including humans, Cyp26b1 expression is not downregulated during meiosis (Frydman et al, 2017). Cyp26b1 has a central role in suppressing meiosis in embryonic testes in mice, and is not expressed in developing ovaries during meiotic initiation.…”
Section: Future Directionsmentioning
confidence: 97%
“…Cyp26b1 has a central role in suppressing meiosis in embryonic testes in mice, and is not expressed in developing ovaries during meiotic initiation. However, in other organisms, including humans, Cyp26b1 expression is not downregulated during meiosis (Frydman et al, 2017). A recent comparative study with marsupials concludes that the roles of RA and Stra8 are conserved in the initiation of meiosis across Therian mammals while that of Cyp26b1 is not (Hickford et al, 2017).…”
Section: Future Directionsmentioning
confidence: 99%
“…However, in the fetal testis, Cyp26b1 degrades RA and prevents the expression of RA‐associated genes including Stra8 , resulting to no entry into meiosis (Bowles et al, ; Koubova et al, ; Kumar et al, ; Li, MacLean, Cameron, Clagett‐Dame, & Petkovich, ; MacLean, Li, Metzger, Chambon, & Petkovich, ). In support of this proposed mechanism, it has been found that in the human fetal ovary, two main meiosis‐preventing factors, Cyp26b1 and FGF9, are expressed in some germ cells and cause Stra8 repression and escape from meiosis (Frydman et al, ).…”
Section: Introductionmentioning
confidence: 93%
“…In human fetal testes, the mechanisms responsible for preventing meiosis are not completely understood (reviewed in Jørgensen & Rajpert-De Meyts 2014). However, several studies have found that CYP26B1 is expressed in both human fetal ovaries and testes, suggesting that, in contrast to mice, this is not a malespecific meiosis inhibitor (Childs et al 2011, Jørgensen et al 2012, Frydman et al 2017. Conversely, the roles of other meiosis-inhibiting factors e.g.…”
Section: Fetal Testis Developmentmentioning
confidence: 99%